2020
DOI: 10.14430/arctic70865
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Alaskan Beaufort Sea by Bowhead Whales (Balaena mysticetus) Tagged with Satellite Transmitters, 2006 – 18

Abstract: We used satellite telemetry to examine bowhead whale movement behavior, residence times, and dive behavior in the Alaskan Beaufort Sea, 2006 – 18. We explored the timing and duration of use of three subregions (western, central, eastern) within the Alaskan Beaufort Sea and applied a two-state switching state-space model to infer bowhead whale behavior state as either transiting or lingering. Transiting whales made direct movements whereas lingering whales changed direction frequently and were presumably feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The strong support for seasonal impacts on foraging behaviour and proximity to the seafloor, along with the seasonal vertical ontogenetic migration of copepods in the Calanidae family (Madsen et al, 2001;, indicate that bowheads were mostly likely exploiting high-energy, diapausing life-stages during fall and winter and surface aggregations of feeding copepods during spring and summer (Madsen et al, 2001;Fortune et al, 2020b). This finding is consistent with the Bering-Chukchi-Beaufort bowhead population that exploit prey aggregations near the sea bottom during fall (Olnes et al, 2020). To a lesser extent, shallow epipelagic dives during early summer may have also reflected consumption of mysids, euphausiids and chaetognaths (Pomerleau et al, 2012).…”
Section: Summary Of Findings and Limitationsmentioning
confidence: 68%
See 1 more Smart Citation
“…The strong support for seasonal impacts on foraging behaviour and proximity to the seafloor, along with the seasonal vertical ontogenetic migration of copepods in the Calanidae family (Madsen et al, 2001;, indicate that bowheads were mostly likely exploiting high-energy, diapausing life-stages during fall and winter and surface aggregations of feeding copepods during spring and summer (Madsen et al, 2001;Fortune et al, 2020b). This finding is consistent with the Bering-Chukchi-Beaufort bowhead population that exploit prey aggregations near the sea bottom during fall (Olnes et al, 2020). To a lesser extent, shallow epipelagic dives during early summer may have also reflected consumption of mysids, euphausiids and chaetognaths (Pomerleau et al, 2012).…”
Section: Summary Of Findings and Limitationsmentioning
confidence: 68%
“…Consequently, estimates of annual and even daily foraging effort must be extrapolated beyond the available data (e.g., Savoca et al, 2021). This contrasts with what long-term satellite telemetry and time-depth recorder data have revealed for both the eastern (Laidre and Heide-Jorgensen, 2012;Nielsen et al, 2015;Chambault et al, 2018;Fortune et al, 2020c) and western (Citta et al, 2015;Olnes et al, 2020;Citta et al, 2021) bowhead whale populations.…”
Section: Seasonality In Foraging Behaviour and Fastingmentioning
confidence: 91%
“…This is perhaps to be expected, as this area largely serves as a migratory corridor linking summer feeding grounds in the Canadian Beaufort with fall feeding grounds at Utqiaġvik and in the Chukchi Sea. Although feeding is well-documented in the Alaskan Beaufort Sea [e.g., 60,61] feeding events tend to be less consistent and of shorter duration than what is observed within core use areas [e.g., 62,63].…”
Section: Discussionmentioning
confidence: 99%
“…We have also assumed that all whales were in the same behavioral state (migrating). Recent satellite telemetry studies covering 2006-2018 (spanning the years of this study) have shown that 64%-78% of location estimates in the areas of our five sites were classified as "transiting" (Olnes et al, 2020). Therefore, our recordings could also have included sounds from whales that were lingering and/or feeding, presumably FIG.…”
Section: Discussionmentioning
confidence: 99%
“…This staggering of days accounts for the fact that at a mean speed of 5 km/h (see Sec. II E), a bowhead whale could cover the 280 km between sites 5 and 1 in 56 h, or 2.3 days, though they likely take longer (Olnes et al, 2020). The end of data collection varied between sites and years, occurring between 28 September and 12 October (Table I).…”
Section: Defining the Migration Sampling Periodmentioning
confidence: 99%